Reference values for accelerometer metrics and associations with cardiorespiratory fitness: a prospective cohort study of healthy adults and patients with heart failure - Fabian Schwendinger; Jonathan Wagner; Raphael Knaier; Denis Infanger; Alex V. Rowlands; Timo Hinrichs; Arno Schmidt-Trucksäss (Current Issues in Sport Science, 2023)
Background